Emergency scrotal exploration in children: Following a change in mindset in the UK - Gopal, Milan; Thattaruparambil, Vinayak; McLaran, Pearly; Weisser, Swantje; Auth, Janina (Journal of Pediatric Urology, 2023)
A survey of 200 emergency scrotal explorations done over four paediatric surgical centres in the UK revealed that the incidence of finding testicular torsion (TT) was 24% and the preoperative utilisation of Doppler ultrasound (DUS) was 10% [1]. We changed our practice to include better preoperative utilisation of a clinical risk score (TWIST) and DUS. This led to a significant increase in the incidence of finding TT from 18% to 53%. Obtaining a DUS did not lead to an increase in our orchidectomy rate. Adopting this change is possible in an NHS setting and it has significant clinical and economic benefits.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Doppler ultrasound; Testicular torsion; TWIST; UK